Facile synthesis of micro-spherical LiMn0.7Fe0.3PO4/C cathodes with advanced cycle life and rate performance for lithium-ion battery. Issue 6 (15th April 2017) - Yang, Li; Wang, Yan; Wu, Jinhua; Xiang, Mingwu; Li, Jianlong; Wang, Boya; Zhang, Yun; Wu, Hao; Liu, Heng
Abstract: A series of micro-spherical LiMn0.7 Fe0.3 PO4 /C (LMFP) cathode materials are synthesized via co-precipitation method combining spray drying and solid-state reaction. All as-prepared materials are well-characterized to determine their crystal structure, morphology and electrochemical performance. All as-obtained LMFP materials correspond to orthorhombic olivine structure with Pbnm space group and show uniform porous spherical structure with an average particle size of 3 µm and a carbon coating layer of about 3 nm. In particular, the resulting LMFP material prepared at 600 °C exhibits a high discharge capacity of 160 mAh g −1 at 0.1 C. Even at a high rate of 10 C, it can still deliver 133 mAh g −1 and maintain capacity retention of 84.9% after 200 cycles. The excellent electrochemical performance is ascribed to the synergetic effect of porous micro-spherical structure and uniform carbon coating layer.